Administrasi dan Ilmu Pendidikan Sebuah Pendekatan Interdisipliner - Sudin, Mokhtaridi (Institut Agama Islam Negeri (IAIN) Metro, 2016)
This paper discusses the Administration and science education. The second thing is a series of the parcel, which each have their own background and historical. Only on the second level the application of disciplines that have real relevance in terms of the achievement of the objectives of education in General. To see a more complex administrative linkages with a view the goals and concepts contained in the science education, many approaches that can be used. One of the approaches that try to use in the writing of this interdisciplinary approach is to actually see the Administration as science and science education as a science education that did not yet completely to integration between the two. After viewing each then imaged will be where the Administration and science education have one of the same architecture. To reaffirm the direction of orientation better education is needed about the deepening administration led to the education administration in the concept of management of parts of the great purpose of education.